Using Creative Activities to Develop High School Students’ Writing Skills - Rakhymbekova, Venera (FKIP - Universitas Riau, 2025)
High school students often face challenges in developing essential writing skills for academic and professional success. Integrating creative activities into the classroom has proven to be an effective way to address these issues. This article examines the use of storytelling, reflective journaling, collaborative writing projects, and gamification as innovative tools to enhance students’ writing abilities. These activities not only foster creativity but also improve students’ engagement, critical thinking, and self-expression. The study combines theoretical insights with practical applications, supported by case studies and recent research findings. Results show significant improvements in writing fluency, coherence, and originality among students who participated in creative tasks. Challenges in implementing these methods, such as time constraints and varying student engagement levels, are also discussed, along with potential solutions. The findings emphasize the importance of a supportive and interactive learning environment in developing high school students’ writing skills.